Two polyketide synthases are necessary for 4‐hydroxy‐5‐methylcoumarin biosynthesis in Gerbera hybrida. (19th July 2016) - Pietiäinen, Milla; Kontturi, Juha; Paasela, Tanja; Deng, Xianbao; Ainasoja, Miia; Nyberg, Paulina; Hotti, Hannu; Teeri, Teemu H.
Summary: Gerbera ( Gerbera hybrida ) is an economically important ornamental species and a model plant of the Asteraceae family for flower development and secondary metabolism. Gerberin and parasorboside, two bitter tasting glucosidic lactones, are produced in high amounts in nearly all gerbera tissues. Gerbera and its close relatives also produce a rare coumarin, 4‐hydroxy‐5‐methylcoumarin (HMC). Unlike most coumarins, 5‐methylcoumarins have been suggested to be derived through the acetate‐malonate pathway. All of these polyketide‐derived glucosylated molecules are considered to have a role in defense against herbivores and phytopathogens in gerbera. Gerbera expresses three genes encoding 2‐pyrone synthases ( G2PS1–3 ). The enzymes are chalcone synthase‐like polyketide synthases with altered starter substrate specificity. We have shown previously that G2PS1 is responsible for the synthesis of 4‐hydroxy‐6‐methyl‐2‐pyrone (triacetolactone), a putative precursor of gerberin and parasorboside. Here we show that polyketide synthases G2PS2 and G2PS3 are necessary for the biosynthesis of HMC in gerbera, and that a reductase enzyme is likely required to complete the pathway to HMC. G2PS2 is expressed in the leaf blade and inflorescences of gerbera, while G2PS3 is strictly root specific. Heterologous expression of G2PS2 or G2PS3 in tobacco leads to the formation of 4, 7‐dihydroxy‐5‐methylcoumarin, apparently an unreduced precursor of HMC, while ectopic expression in gerbera leads to HMC formation in tissues where nontransgenic tissue does not express the genes and does not accumulate the compound. Using protein modelling and site‐directed mutagenesis we identified the residues I203 and T344 in G2PS2 and G2PS3 to be critical for pentaketide synthase activity. Significance Statement: Coumarins are thought to play roles in plant defense, but the enzymes required for biosynthesis of the polyketide‐derived 4‐hydroxy‐5‐methylcoumarin were not known. Here we identify and characterize the responsible polyketide synthases.